Penerapan Model Pembelajaran Windows Shopping Dikolaborasikan Ddengan Project Based Learning (PJBL) Sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Ekonomi di Kelas X-IPS 3 SMAN 1 GEDEG - Astutik, Siska Widya; Kurniawan, Riza Yonisa; Wahyuningtyas, Endar (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2023)
This study aims to improve student learning outcomes in economics lessons in class X-IPS 3 SMAN 1 GEDEG. This type of research is classroom action research. This study used the windows shopping learning model in collaboration with PJBL (Project Based Learning). This research was carried out over two cycles, each cycle consisting of planning, observing, implementing, and reflecting. The results obtained from the first cycle research showed an average acquisition value of 78.1 and the average acquisition value obtained from the research results in the second cycle was 95.8. So it can be concluded that the application of the windows shopping learning model in collaboration with PJBL (Project Based Learning) can improve student learning outcomes in economics subjects in class X-IPS 3 SMAN 1 GEDEG.